PENGEMBANGAN KLASTER UMKM DALAM UPAYA PENINGKATAN DAYA SAING USAHA - Sumaryana, Fitriana Dewi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
From a world perspective, it has been acknowledged that micro, small and medium enterprises (MSMEs) play a vital role in development and economic growth, not only in developing countries but also in developed countries. In Developed Countries, MSMEs are important not only because they absorb the largest number of workers but also in many countries their contribution to the formation or growth of gross domestic product (GDP) is greater than the contribution of big business. The current policy of MSME development is still not optimal. Therefore, stakeholders, government and agencies should make efforts to improve the competitiveness of leading commodities in order to win the competition at the global level. The development of MSME is an integral part of the economic unification among ASEAN member countries. So far, government policies related to UMKM mostly use social welfare approach rather than business approach. The SME cluster is a system that supports the progress of SMEs, SME clusters form internal and external networks to gain economic benefits and enhance competitiveness.